Peran Literasi Pajak dalam Memoderasi Pengaruh Kesadaran dan Sanksi Terhadap Kepatuhan Pajak Kendaraan Bermotor (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyse the influence of tax awareness and tax penalties on compliance with motor vehicle tax payments in the West Surabaya region, as well as to examine the role of tax literacy as a moderating variable. The study employs a quantitative approach using primary data collected through the distribution of questionnaires to 86 motor vehicle taxpayers at the West Surabaya Samsat office. The data were analysed using statistical analysis techniques to test the direct effects between variables and the moderating effect of tax literacy. The results indicate that tax awareness does not have a significant effect on compliance with motor vehicle tax payments, whereas tax penalties have a significant effect on the level of compliance. These findings suggest that taxpayer compliance is more influenced by external factors, such as penalties, than by internal factors, such as awareness. The results of the moderation test show that tax literacy moderates the relationship between tax awareness and compliance in a negative direction, meaning that the higher the tax literacy, the weaker the influence of tax awareness on compliance. Meanwhile, tax literacy does not moderate the relationship between tax sanctions and compliance with motor vehicle tax payments. The findings of this study suggest that efforts to improve tax compliance should focus on the consistent application of penalties and on enhancing tax literacy—not merely in an informative capacity, but in a way that is capable of driving behavioural change among taxpayers.